2005
DOI: 10.1523/jneurosci.1476-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Neuregulin Restores Radial Glia in a (Ferret) Model of Cortical Dysplasia

Abstract: Radial glia are integral components of the developing neocortex. During corticogenesis, they form an important scaffold for neurons migrating into the cortical plate. Recent attention has focused on neuregulin (NRG1), acting through erbB receptors, in maintaining their morphology. We developed a model of developmental radial glial disruption by delivering an antimitotic [methylazoxy methanol (MAM)] to pregnant ferrets on embryonic day 24 (E24). We previously found that normal ferret cortex contains a soluble f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Moreover, exogenous application of NRG1 restores radial glial morphology in E24 MAM-treated cortex and acts via ErbB3 and ErbB4 receptor signaling (Gierdalski et al, 2005). In the current study we restore the migration pattern of cells leaving the GE by rescuing radial glia morphology.…”
Section: Ngr1 Restores Tangential Migrationmentioning
confidence: 48%
See 1 more Smart Citation
“…Moreover, exogenous application of NRG1 restores radial glial morphology in E24 MAM-treated cortex and acts via ErbB3 and ErbB4 receptor signaling (Gierdalski et al, 2005). In the current study we restore the migration pattern of cells leaving the GE by rescuing radial glia morphology.…”
Section: Ngr1 Restores Tangential Migrationmentioning
confidence: 48%
“…We recently demonstrated that neuregulin (NRG1) added to the media of E24 MAM-treated cultures restores the elongated morphology of radial glial cells (Gierdalski et al, 2005). To determine if restored radial glia morphology improves the ability of tangentially migrating cells to reach the CP, we added NRG1 to the media of normal and E24 MAM-treated organotypic cultures and injected DiI into the GE.…”
Section: Normal Rg Morphology Is Necessary For the Proper Positioningmentioning
confidence: 99%
“…Radial glia maintenance and/or differentiation results from a balance between neurogenic and stem cell-maintaining molecules such as neuregulin-1 and Notch1 [14,15,16,17,73,74,75,76,77,78,79], and differentiating molecules such as TGF-β 1 [26,80], cardiotrophin [25] and ciliary neurotrophic factor [18], which are crucial to control the correct timing of the neurogenic-to-gliogenic switch of radial glia cells. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study showed that treatment of MAMexposed slices with neuregulin was sufficient to rescue radial glial defects but not Cajal-Retzius cell positioning defects (Gierdalski et al, 2005). This suggested that marginal zone defects after MAM exposure are reversible and that a teratogenic insult might cause marginal zone dysplasia by affecting only a small number of molecular pathways.…”
Section: Disruption Of the Marginal Zone After Mam Exposurementioning
confidence: 99%